2021
DOI: 10.1017/s1355617721000515
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Profile of Intellectually Gifted Children: A Systematic Review

Abstract: Objective: The term intellectually gifted (IG) refers to children of high intelligence, which is classically measured by the intelligence quotient (IQ). Some researchers assume that the cognitive profiles of these children are characterized by both strengths and weaknesses, compared with those of their typically developing (TD) peers of average IQ. The aim of the present systematic review was to verify this assumption, by compiling data from empirical studies of cognitive functions (language, motor skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…This heterogeneity encourages the use of a wider concept of intelligence, such as the multiple intelligence perspective [ 3 , 4 ]. More importantly, it suggests that a more appropriate approach should be capitalizing on inter-individual variability in cognitive functioning instead of delineating a unique profile of functioning that encompasses all gifted individuals, as outlined by a recent review on neuropsychological functioning in high IQ individuals [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity encourages the use of a wider concept of intelligence, such as the multiple intelligence perspective [ 3 , 4 ]. More importantly, it suggests that a more appropriate approach should be capitalizing on inter-individual variability in cognitive functioning instead of delineating a unique profile of functioning that encompasses all gifted individuals, as outlined by a recent review on neuropsychological functioning in high IQ individuals [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In physics problem solving, Coleman and Shore (1991) reported that experts and high-achieving students had advantages over averageachieving students in that they made the best of prior knowledge and accurately monitored and evaluated their mental processes. Yet it should be noted that not all gifted individuals have advantages in specific domains (for a review, Bucaille et al, 2022). Their performance may vary depending on the match between task requirements and their strengths.…”
Section: Stem Achievement Of Learners With Diverse Backgroundsmentioning
confidence: 99%
“…Intelligence can be seen as the ability to recognize and understand reality and use knowledge and experience to solve problems such as memory, observation, imagination, thinking, and judgment. Gifted children are regarded to have higher intelligence and perform better in attention, language, mathematics, verbal working memory, shifting, and social problem-solving (Bucaille et al, 2022 ). At the same time, gifted children demonstrate high working memory capacity and more effective executive attention (Aubry et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%